Satisfacción laboral del personal de enfermería y clima organizacional en el servicio de enfermería del Hospital Regional Docente de Trujillo - Sanchez Murillo, Jhen Ere Sandibel (2016)
This research study, descriptive - correlational was held at Regional Hospital of Trujillo (HRDT) during the months of January-February 2014, in order to determine the level of job satisfaction of nurses Service emergency and organizational climate in the service. The sample consisted of 27 nurses who met the inclusion criteria. Instruments used to collect data: a survey to determine the level of job satisfaction of nurses and survey to determine the organizational climate and the information obtained, processed and analyzed using the statistical test of "Chi cuadrardo"; the results are presented in graphs and crosstab. After the analysis has led to the following conclusions: - The level of job satisfaction among nurses Emergency Service Regional Hospital of Trujillo is 13% to a low level of satisfaction, 82.6% to an average level of satisfaction and 4.3% for a high level of satisfaction. -The Organizational climate Emergency Service Trujillo Regional Hospital is determined to be unfavorable for 39.1 of their nurses, fairly favorable by 34.8%, favorably by 17.4% and most favorably by 8.7% of human resources in the study. He found that there is significant relationship between job satisfaction of nurses emergency service Regional Hospital of Trujillo and organizational climate.